2019
DOI: 10.1101/19009795
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influenza forecasting for the French regions by using EHR, web and climatic data sources with an ensemble approach ARGONet

Abstract: Effective and timely disease surveillance systems have the potential to help public health officials design interventions to mitigate the effects of disease outbreaks. Currently, healthcare-based disease monitoring systems in France offer influenza activity information that lags real-time by 1 to 3 weeks. This temporal data gap introduces uncertainty that prevents public health officials from having a timely perspective on the population-level disease activity. Here, we present a machine-learning modeling app… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Previous methods, such as the ARGONet model [ 11 , 45 ], have been shown to make accurate real-time prediction at the state level in the United States for seasonal infectious diseases such as influenza. In addition, Chinazzi et al [ 16 ] showed that it was possible to estimate the evolution of an emerging outbreak using a mechanistic model.…”
Section: Discussionmentioning
confidence: 99%
“…Previous methods, such as the ARGONet model [ 11 , 45 ], have been shown to make accurate real-time prediction at the state level in the United States for seasonal infectious diseases such as influenza. In addition, Chinazzi et al [ 16 ] showed that it was possible to estimate the evolution of an emerging outbreak using a mechanistic model.…”
Section: Discussionmentioning
confidence: 99%
“…We generated ensemble model estimates, consistent with the first ARGONet procedure described in Poirier et al 35 by assigning the point estimate for a given month to that of the DIM, NM, and NM2, depending on which model yielded the lowest rRMSE for the prior three months [24,35]. We assigned the mean across models as the point estimate for the first three months of observations.…”
Section: Data Inputs and Methods Of Training And Testing The Two Network Modelsmentioning
confidence: 99%
“…To provide decision-makers with a prospective uncertainty quantification (error bars) of our estimates, we constructed 95% confidence intervals by considering the error (RMSE) of model predictions for the prior 24 months, starting with January 2009 (two years after the first out-of-sample prediction). Subsequently, following an approach outlined in Poirier et al [ 35 ] citing work by Yang et al [ 36 ] to capture changing uncertainty at different points in time, we generated the lower and upper limits of the confidence intervals by subtracting or adding the RMSE associated to a moving window of the last 24 errors, respectively, to the upcoming point estimate [ 35 , 36 ]. This confidence interval construction is well-justified as we found that the RMSEs broadly reflected the standard deviation (STD) of the distribution of residuals (predictions—eventually reported or “true” case counts) for each time point ( S7 Fig ) [ 35 , 36 ], and thus, assuming that our residuals are Gaussian distributed, 95% of residuals should be captured within the mean (the point estimate) plus and minus the STD of residuals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation